STUDI KOMPARASI ANTARA PENERAPAN PEMBELAJARAN KOOPERATIF TIPE STAD DAN PEMBELAJARAN KONVENSIONAL TERHADAP PRESTASI BELAJAR SISWA MATA PELAJARAN AL-QUR’AN HADIS SISWA KELAS XI TARBIYATUL WATHAN CAMPUREJO PANCENG GRESIK - Ahmad Sulton (Fakultas Agama Islam Universitas Islam Darul 'Ulum Lamongan, 2016)
This study started from that looks phenomena related with the process of learning occurs in senior high school of Tarbiyatul Wathan. As we know that the process of learning occurs in senior high school of Tarbiyatul Wathon looks boring because during the process of learning the teachers just lecture without regard to the wishes of students making learning achievement of students less than the maximum. Therefore researchers offer new strategies in the process of learning namely cooperative learning. In the cooperative learning there is two-way communication mutually in the learning process, for the achievement of optimal learning interactions, finnaly for achievement of maximum learning results.The approach used in this study is a quantitative approach with eksperiment design. For getting data, the researchers went directly to the subject of study for data obtained is valid and accurate, there are two sources of data to be obtained by researchers, namely: respondent and document. In this study, the population is students of class XI IPA and XI IPS senior high school of Tarbiyatul Wathon Campurejo Panceng Gresik totaling is 46 students.The results showed that: (1) There is significant differences between the implementation of STAD cooperative learning and implementation conventional learning on the subject Amar Ma’ruf nahi Mungkar in QS. Ali Imran verse 104, and the hadith to student achievement in XI class senior high school of Tarbiyatul Wathon Campurejo Panceng Gresik, (2) Implementation of STAD cooperative learning is better than conventional learning on the subject Amar Ma’ruf nahi Mungkar in QS. Ali Imran verse 104, and the hadith to student achievement in senior high school of Tarbiyatul Wathan Campurejo Panceng Gresik.